Penyelesaian Sengketa Batas Daerah menggunakan Pendekatan Regulasi (Institut Pemerintahan Dalam Negeri, 2019)
One of the increasing trends in the era of regional autonomy is the regional extension both at the provincial level and at district/city level. However, such situation in some cases has emerged some new problems, such as; social conflict, conflict on natural resourses and conflict in the regional boundaries. This study examines the broblems, first, what factor are causing the dispute on the boundaries in the extension of new autonomous region? Second, how is the pattem of the settlement of boundary dispute provided in the Indonesia legal sistem?Third,what is the role of the Government in solving the boundary dispute? This is a juridical-empirical research. The study concluded that; First, the boundary dispute has been triggered by the area extension processnot requinting the border as a legal requirement in the area expansion. The requirements fulfilled were more technical, physical and political. Second, the pattem of the boundary dispute resolution generally is through two ways; the non-legal border dispute resolution, and legal settlement. In non-legal resolution, it was mediated by MOHA and Govemors; while, in the legal dispute resolution it reached through a judicial review to the Supreme Court or the Constitutional Court. Third, in the dispute of area border, the governments role was the facilitator in accordance with the level of its dispute case.